2007
DOI: 10.1002/cncr.22698
|View full text |Cite
|
Sign up to set email alerts
|

The quality of surgical pathology care for men undergoing radical prostatectomy in the U.S.

Abstract: Amorphous‐made poly(L‐lactide) [i.e., poly(L‐lactic acid) (PLLA)], poly(L‐lactide‐co‐D‐lactide)[P(LLA‐DLA)](77/23), and P(LLA‐DLA)(50/50) films and PLLA films with different crystallinity (Xc) values were prepared, and the effects of molecular weight, D‐lactide unit content (tacticity and optical purity), and crystallinity of poly(lactide) [i.e., poly(lactic acid) (PLA)] on the water vapor permeability was investigated. The changes in number‐average molecular weight (Mn) of PLLA films in the range of 9 × 104–5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…As stated for QI3 and QI4, also the standardization of the pathological evaluation of the prostatectomy specimen plays a central role in the PC patients’ care, the adequate treatment decision planning, such as an eventual adjuvant therapy and the prognosis estimation. In the literature we found only two American studies assessing the quality of surgical pathology reporting [ 48 , 49 ]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As stated for QI3 and QI4, also the standardization of the pathological evaluation of the prostatectomy specimen plays a central role in the PC patients’ care, the adequate treatment decision planning, such as an eventual adjuvant therapy and the prognosis estimation. In the literature we found only two American studies assessing the quality of surgical pathology reporting [ 48 , 49 ]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the genitourinary malignancy literature, Miller et al. [23] evaluated prostate cancer reporting after radical prostatectomy. Overall, these authors found good compliance with standards, although stage and tumour size descriptions were absent in half of the reports.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Miller et al. [23] was conducted among only Commission on Cancer designated programmes, whereas the present study included sites without a relationship to a national standards‐setting body.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are ample data to demonstrate a relationship between quality of care and outcomes in the treatment of prostate cancer, no previous comparative effectiveness study in prostate cancer has attempted to control for the quality of the intervention [26,52,60,61]. The CEASAR study is unique in this regard and we anticipate that patients will be able to use our results to guide not only treatment decisions, but also provider and facility decisions.…”
Section: Commentmentioning
confidence: 99%